1986
DOI: 10.1152/jappl.1986.60.2.716
|View full text |Cite
|
Sign up to set email alerts
|

Ear oximetry during combined hypoxia and exercise

Abstract: Ear oximetry is widely used to detect arterial O2 desaturation during exercise in patients with cardiopulmonary disease. Although oximeters have been evaluated for accuracy, response time, and the influence of skin pigmentation, tests of their reliability have not been reported during strenuous exercise. Accordingly, we compared arterial O2 saturation (Sao2) measurements obtained by Hewlett-Packard (HP, model 47201A) and Biox II oximeters with those determined directly from arterial blood in six healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…The SEE obtained in this study (1.8) was lower than that obtained with the Hewlett-Packard (4.1) and Biox II (5.4) evaluated by Smyth et al (1986). The discrepancy between these two studies could be due to the dierent protocols used.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The SEE obtained in this study (1.8) was lower than that obtained with the Hewlett-Packard (4.1) and Biox II (5.4) evaluated by Smyth et al (1986). The discrepancy between these two studies could be due to the dierent protocols used.…”
Section: Discussioncontrasting
confidence: 78%
“…The accuracy of dierent oximeters during normoxic exercise (Breuer et al 1990;Norton et al 1992) or hypoxic exercise (Smyth et al 1986;Martin et al 1992) has been evaluated. While some authors have shown that pulse oximeters provide a valid predictor of percentage saturation of haemoglobin with oxygen (%HbO 2 ; Powers et al 1989;Barthe le my et al 1990;Breuer et al 1990;Martin et al 1992), other authors (Smyth et al 1986;Norton et al 1992) suggest that pulse oximetry has serious limitations during exercise. The dierences in oximeters used (Barthe le my et al 1990) and in the intensity of exercise (Norton et al 1992) may explain these discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…The oximeter was calibrated using an internal protocol before each test according to the manufacturer's instructions. This instrument has been reported to be accurate across a wide range of SaO2, with arterial SaO2 values >75% underestimated by <2% (31 ). The "older" HP 47201A oximeter is unique because it uses eight wavelengths covering the range from 650 to 1050 nm and 18 molar extinction coefficients to detennine oxy-and deoxyhemoglobin concentrations, whereas most modem oximeters use only two or three wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…The reliability of oximetry during exercise has been questioned [14,15] when Sp,O 2 values below 90% are recorded [15,16], and particularly when evidence of hypoxia exists in connection with exercise [17]. On the other hand, several studies have demonstrated that oximetry provides accurate measures of arterial oxygen saturation (Sa,O 2 ) in subjects breathing hypoxic gas mixtures [18,19], as well as in normal subjects [20], pulmonary patients [21], and trained athletes [22] during exercise.…”
mentioning
confidence: 99%